Incidence and predictors of severe obstetric morbidity in a teaching hospital - Bajagain, Rupa; Saha, Rachana Saha (Journal of Kathmandu Medical College, 2017)
Background: Evaluation of severe obstetric morbidity is an important aspect of optimum maternal health. Towards this, the Water stone and Mantel criteria have been used to know the incidence, predictors and causes of severe obstetric morbidity.Objectives: The study aimed to estimate incidence, predictors and causes of obstetric morbidity at Kathmandu Medical College and Teaching Hospital.Methods: A hospital-based prospective study was carried out from 1st September 2014 to 31st August 2015. All cases of severe obstetric morbidity according to the Mantel and Water stone criteria were identified. The socio-demographic and healthcare characteristics of extremely severe cases were compared with controls which included women who were admitted before and after the indexed cases.Results: There were 2270 deliveries during the study period, out of which 74 cases of severe obstetric morbidities were identified i.e. an incidence of 32.5 per 1000 deliveries. During the study period, there were three maternal deaths attributed to conditions studied. Disease-specific morbidities per 1000 deliveries were 18.9 for haemorrhage, 9.2 for severe pre-eclampsia, 0.88 for eclampsia, 0.44 for haemolysis elevated liver enzyme and low platelet count and 3.08 for sepsis. A total of 26 patients were admitted in Intensive care unit which was 1.145 per 100 of total deliveries.Conclusion: Severe obstetric morbidity and its relation to mortality may be more sensitive measures of pregnancy outcome than mortality alone. In this study, most events are related to obstetric haemorrhage and severe pre-eclampsia.Journal of Kathmandu Medical College Vol. 5, No. 2, Issue 16, Apr.-Jun., 2016, page: 44-48